Essays in post-Keynesian inflation - Gapinski, James H.; Rockwood, Charles Edward; Lerner, Abba Ptachya (Cambridge, Mass. : Ballinger Pub. Co., 1979)
This volume contains a collection of new essays which evolved from a conference on inflation held in honour of Abba P. Lerner, March 28-30, 1979 at Florida State University.
Papers presented in honor of A. P. Lerner.
Includes bibliographical references and indexes.
osc 3/5/18
Loans
Keywords: Lerner, Abba Ptachya; Inflation (Finance)